Over a million students use our free study notes to help them with their homework
Quadratic formula: where ax^2+bx+c =0, x = (-b±√(b^2-4ac))/2a.Rearrange the formula in the question to get 3x^2+4x-20 = 0.From the quadratic in the question we can see that a = 3, b = 4, c = -20.Therefore...
The correct answer is: 4x+3. The first part of the equation is differentiated by multiplying the power by the constant in front (2*2). The power is then reduced by one to x^1 (which is just x). This ...
The format of this question shows that it is a quadratic, which we can solve by factorising. We have 3 methods by which we can do this:First, we need to manipulate the eq...
Start off by determining which unknowns have the same coefficient- In this case it would be y as the coefficient of y is 1 in both equationsThen make both equations equal to y- So 3x+y= 11 would...
fg(x) = 3(2ax +1) - 2a = 6ax + 3 - 2a6ax + 3 -2a = 2x + b/26a = 2 -> a = 1/33 - 2a = b/2 -> if a = 1/3 then: 3 - 2(1/3) = 9/3 - 2/3 = 7/3 7/3 * 2 = b = 14/3
←
529
530
531
532
533
→
Internet Safety
Payment Security
Cyber
Essentials